Helping feed the world with rice innovations: CGIAR research adoption and socioeconomic impact on farmers - Mishra, Ashok K.; Pede, Valerien O.; Arouna, Aminou; Labarta, Ricardo Antonio; Andrade, Robert Santiago; Veettil, Prakashan Chellattan; Bhandari, Humnath; Laborte, Alice G.; Balie, Jean; Bouman, Bas (Elsevier, 2022)
Rice production has increased significantly with the efforts of international research centers and national governments in the past five decades. Nonetheless, productivity improvement still needs to accelerate in the coming years to feed the growing population that depends on rice for calories and nutrients. This challenge is compounded by the increasing scarcity of natural resources such as water and farmland. This article reviews 17 ex-post impact assessment studies published from 2016 to 2021 on rice varieties, agronomic practices, institutional arrangements, information and communication technologies, and post-harvest technologies used by rice farmers. From the review of these selected studies, we found that stress-tolerant varieties in Asia and Africa significantly increased rice yield and income. Additionally, institutional innovations, training, and natural resource management practices, such as direct-seeded rice, rodent control, and iron-toxicity removal, have had a considerable positive effect on smallholder rice farmers’ economic well-being (income and rice yield). Additional positive impacts are expected from the important uptake of stress-tolerant varieties documented in several Asian, Latin American, and African countries.